Dampak Konvergensi Media Terhadap Pola Menonton Televisi Indonesia di Era Digital (Jurnal Kajian Media, 2021)
The present digital era is marked by the emergence of computer technology and other technologies that support electronic access to information. Various digital media that are connected to each other form a new media that is more compatible, easily and quickly accessed, which is then called media convergence. During its development, this has led to various changes in the mass media on how information is presented to the public. In this regard, the television media is no exception, which has undergone several changes due to media convergence. YouTube is a platform that is considered to be one of the most compatible forms of media convergence with television characters. This research focuses on how audiences or television viewers enjoy Indonesian television programs on the YouTube platform, which is analyzed from the number of viewers to see the viewing patterns and measure the impact of media convergence on television. The results of this study can provide an up-to-date picture of how Indonesians watch television and what steps have been taken by television stations in dealing with these impacts. Keywords: media convergence, television, YouTube, digital, information.